Perancangan E-Catalog Produk guna Mempromosikan Produk Plakat pada Putri Advertising - M. Irfan Tarmizi; Lailla, Nor; Gunawan Hidayat; Restika Eka Pratiwi (Politeknik Piksi Ganesha Indonesia, 2025)
In today's digital era, product marketing activities are not only carried out conventionally. Business actors such as Putri Advertising need promotional media that are more effective, attractive, and easily accessible to consumers widely, one of which is through the creation of a plaque e-catalog as a digital promotional media. The purpose of this activity is to increase the competitiveness of business actors and the creation of a professional e-catalog that can be used as a partner marketing tool. The method of this activity is mentoring the creation of a plaque e-catalog. As a result, with this e-catalog, it is hoped that the reach of plaque marketing will be wider, increase selling value, and strengthen Putri Advertising's existence in the competition of the creative industry.